Pengaruh Inovasi Produk dan Kepuasan terhadap Loyalitas Pelanggan pada Menu Es Cendol di Yoshinoya AEON Jakarta Garden City - Nadya Farhana; Purwatiningsih Purwatiningsih (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Customer loyalty plays a crucial role in influencing sales performance and ensuring the sustainability of a fast-food restaurant. Therefore, strategies to foster customer loyalty must be implemented through continuous product innovation and enhanced customer satisfaction. This study aims to analyze the effect of product innovation and customer satisfaction on customer loyalty, with a specific focus on the iced cendol menu at Yoshinoya AEON Jakarta Garden City. The research employed a descriptive quantitative approach with a sample of 100 respondents selected using a specific sampling technique. Data were collected through observation, questionnaires, and documentation, and subsequently analyzed using the t-test for partial testing and the F-test for simultaneous testing. The results of the study indicate that product innovation has a significant partial effect on customer loyalty, as evidenced by a probability value of 0.000 < 0.05 and a t-count value of 5.287, which is greater than the t-table value of 1.98472. Furthermore, customer satisfaction also shows a significant partial effect on customer loyalty, supported by a probability value of 0.000 < 0.05 and a t-count value of 4.213, exceeding the t-table value of 1.98472. Simultaneous testing further reveals that product innovation and customer satisfaction together have a significant influence on customer loyalty, as shown by a probability value of 0.000 < 0.05 and an F-count value of 57.609, which is greater than the F-table value of 3.090. Thus, this research emphasizes that relevant product innovations combined with improved customer satisfaction play a vital role in strengthening customer loyalty, ultimately enhancing the competitiveness of fast-food restaurants amid an increasingly intense culinary industry.